PROFIL PENCAPAIAN TUGAS PERKEMBANGAN ANAK DI SD NEGERI 16 PULAU KARAM KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Sari, Rahmi Kurnia (Bimbingan dan Konseling, 2014)
This research is motivated by the task of child development that has not been achieved. The purpose of this study was to describe the childs attainment of developmental tasks. This research is descriptive quantitative. Sampling was performed using total sampling totaling 50 people. Data analysis used the percentage techniques. The results of this study revealed that: 1) The task of the childs development in learning physical skills that are used for common games has been reached. 2) The task of child development in developing notions needed for daily life has attained 3) The task of the development of children in developing basic skills for reading less achieved. 4) The task of child development in a developing conscience, morals and religion has been reached.